Molecular identification and genotyping of Streptococcus mutans from saliva samples of children in Medellin, Colombia (2014)
ABSTRACT: Introduction and objective: Tooth decay is one of the most prevalent infectious diseases of the oral cavity. The aim of this study was to determine the prevalence of Streptoccocus mutans and its genotypes in saliva samples from 6 and 7 year old children with and without dental caries. Materials and methods: Forty seven saliva samples were obtained from 6-7 year-old children, randomly selected from a Public School in Medellin, Colombia. Oral examinations in order to determine the DMF-T Index (Decay, Missing and Filling Teeth) were carried out. Isolates were identified by the Streptoccocus sobrinus and Streptococcus mutans PCR, API 20STREP and 16S rRNA sequence analysis. Genotypes c, e, f and k were detected by PCR. Results: Prevalence of S. mutans was 14.9%. Of the 47 saliva samples, 57.4% (27) corresponded to children with dental caries, and 8.5% (4) were positive for S. mutans genotype c, 2.1% (1 each) genotype f, genotype k, and genotype c and k, respectively. Conclusion: Prevalence of S. mutans was lower than in previous studies of Colombian children with similar demographic characteristics. Streptoccocus mutans genotype c, f and k were found in children with caries but not in the group without caries. This is the first report of S. mutans genotype K in Colombia; this genotype requires further study to clarify its relation with dental caries and cardiovascular disease in Colombia.